The Annual costs of treating genital warts in the Public Healthcare Sector in Peru - Enrique M Saldarriaga; Cesar P. Cárcamo; Joseph B. Babigumira; Patricia J. García (BMC, 2021)
Abstract Objectives To estimate the cost of six different techniques used to treat Genital Warts and the annual average cost of treating a typical GW patient in Peru. To estimate the annual economic burden diagnosing and treating GW in the Peruvian public healthcare system. Methods We developed a prevalence-based, cost-of-illness study from the provider's perspective, the healthcare facilities under the purview of Peruvian Ministry of Health. We used an activity-based costing approach. We conducted primary data collection in three regions in Peru and supplemented it with governmental data. Uncertainty of the costing estimates was assessed via Monte Carlo simulations. We estimated the average cost and associated confidence intervals for six treatment options - three topical and three surgical - and the overall cost per patient. Results The average treatment cost per patient was 59.9USD (95 %CI 45.5, 77.6). Given a population of 18.4 million adults between 18 and 60 years of age and a GW prevalence of 2.28 %, the annual cost of treating GW was 25.1 million USD (uncertainty interval 16.9, 36.6). Conclusions This study provides the first quantification of the economic burden of treating genital warts in Peru and one of the few in Latin America. The costing data did not include other healthcare providers or out-of-pocket expenditures, and hence we present a conservative estimate of the COI of GW in Peru. Our findings bring attention to the financial burden of treating GW, a vaccine-preventable disease.